Prarancangan Pabrik Sodium Silikat Dari Natrium Hidroksida Dan Pasir Silika Kapasitas Produksi 60.000 Ton/Tahun - Trisnian, Nanda, M. Mujiburohman, S.T. M.T. Ph.D, Rois Fathoni, S.T. M.Sc. Ph.D (2016)
Sodium silicate factory with raw material sodium hydroxide and silica sand, the production capacity of 60.000 tons per year is planned to operate for 330 days per year. This factory will be established in an industrial area Gresik, East Java, with a land area of 12,168 m2 and the number of employees is 188 people. The process of producing sodium silicate is performed using continuous stirred tank reactor (CSTR) by way reacting sodium hydroxide and silica sand. In the reactor the reaction undergoes liquid-liquid phase, endothermic, with operating temperatures of 220oC and a pressure of 24 bar. To produce 8,850.50 kgs/hour sodium silicate. The process requires raw materials including 3,316.43 kgs/hour of sodium hydroxide, and 6,276.16 kgs/hour of silica sand. The process also needs utility including 62,189.20 kgs/hour of water, 8,175.91 kgs/hour of steam, 173.36 liters/hour of diesel fuel, and 502.68 kW of electricity. The sodium silicate factory requires production costs of Rp256,437,791,787.00. The economic analysis of this plant showed a profit before tax of Rp65,156,021,370.00 per year, after tax profits reached Rp48,867,016,027.00 25% per year. The return on investment (ROI) before tax 27,8% and 20,8% after taxes. The pay out time (POT) before tax was 2.65 years and 3.25 years after tax. The break even point (BEP) was 53.43% and Shut down point (SDP) amounted to 28.26%. The discounted cash flow (DCF) accounted for 46.05%. From those economic it is analysis concluded that the plant is profitable and feasible to set.